Phase Synchronization in Coupled Sprott Chaotic Systems Presented by Fractional Differential Equations - G. H. Erjaee; M. Alnasr (Discrete Dynamics in Nature and Society)
Phase synchronization occurs whenever a linearized system describing the evolution of the difference between coupled chaotic systems has at least one eigenvalue with zero real part. We illustrate numerical phase synchronization results and stability analysis for some coupled Sprott chaotic systems presented by fractional differential equations.